Genetic relationships among Arachis species based on AFLP - Gimenes, Marcos A. [UNESP]; Lopes, Catalina R. [UNESP]; Valls, Jose F.M. (Sociedade Brasileira de Genética, 2002)
Amplified Fragment Length Polymorphism (AFLP) was used to establish the genetic relationships among 20 species from seven of the nine sections of genus Arachis. The level of polymorphism among nine accessions of the cultivated peanut, A. hypogaea L., was also evaluated. Three combinations of primers were used to amplify the AFLPs. The fragments were separated in 6% denaturing acrylamide gels. A total of 408 fragments were analyzed. An average of 135.3 fragments per primer combination were scored, and the largest number of fragments was 169 using primer combination Eco RI - ACC / Mse I - CTG, while the lowest was 108, with Eco RI - ACT / Mse I - CTT. In general, the genetic relationships established using AFLPs agreed with the classification established using morphology and crossability data. The results indicated that AFLPs are good markers for establishing the relationships among Arachis species. The polymorphism detected in A. hypogaea by this method was higher than the one found with other markers, like RAPDs and RFLPs. However, our data suggest that the polymorphism detected be using AFLP with only three primer combinations is still too low to be used for any kind of genetic study in this species.
Keywords: AFLP; Arachis; peanut; taxonomic relationship